Supratentorial Tanycytic Ependymoma in an Adult Male: Case Report and Review of Literature - Giselle Lopez; Roger E. McLendon; Katherine B. Peters (Case Reports in Oncology, 2015)
Ependymomas, tumors of the ependymal cells, are very rare and usually present in the pediatric population. Furthermore, there are even rarer variants of ependymomas that can include cellular, papillary, clear cell, and tanycytic subtypes. We present a case of a supratentorial tanycytic ependymoma in an adult male and review the literature in regard to this rare primary central nervous system neoplasm.